A EDUCAÇÃO DIFERENCIADA EM CONTEXTOS MULTICULTURAIS: interfaces de uma nova realidade escolar - Kaliberda, Ana Marcia (2015)
Respect for cultural diversity is essential to promote a harmonious and democratic coexistence in today`s societies. In Brazil, the mixture of various migratory cultures with people already living here, made the Federal Constitution (1988), along with the LDB (1996), seek to ensure the differentiated education to these social groups, respecting their characteristics, history and culture. However, much of the educational practice still sets a homogeneous curriculum. Knowing that differentiated education facing multicultural contexts implies new challenges, the objective of this research is to analyze how is applied this type of education in a school whose brand is precisely the ethnic and cultural diversity. The intention is to argue alternatives under the auspices of intercultural philosophy, which meets the requirements to work the two elements highlighted here, namely differentiated education and multiculturalism. Through participant observation and semi-structured interviews with teachers and school leaders, the research focuses on the methodology used by teachers of the 6th year to promote the process of teaching and learning, comparing it with the intrinsic challenges to the multiethnic profile of the student body of this school.